AUTOMATION TEST MENGGUNAKAN TEKNIK BEHAVIOR DRIVEN DEVELOPMENT PADA APLIKASI GA SYSTEM 2 UNITED TRACTORS - Auliya, Niken Arra Ilma; Aditya, Addin; P., Diah Arifah (Jurnal Teknoinfo, 2024)
Software development that is complex and prone to failures, such as bugs or defects, demands effective testing to ensure quality and reduce the risk of failure during release. This research uses the automation testing method with behavior-driven development (BDD) techniques on the United Tractors GA System 2 Application, focusing on the tender feature. This research aims to test the role of BDD techniques in implementing automation testing on the United Tractors GA System 2 Application and compare test results between automation testing and manual testing methods. The test results show that implementing automation testing with BDD techniques on the United Tractors GA System 2 Application can speed up the testing process, increase time efficiency in application development, and reduce the risk of bugs when released to users. Automation testing also shows a better time ratio, with a ratio of 4:15 on the United Tractors GA System 2 Application tender feature. Based on the research results, it can be concluded that using automation testing with BDD techniques is an effective and efficient approach in software testing, especially in testing the tender feature in the United Tractors GA System 2 Application. The research objective of finding better solutions in software testing has been achieved. Implementing automated testing using BDD techniques on the United Tractors GA System 2 Application provides significant benefits in speeding up the testing process, increasing the efficiency of application development time, and reducing the risk of bugs during release to users. This research proves that testing automation with a BDD approach is an effective solution for improving the quality and overall quality of software testing.Pengembangan perangkat lunak yang kompleks dan rentan terhadap kegagalan, seperti bug atau cacat, menuntut pengujian yang efektif guna memastikan kualitas dan mengurangi risiko kegagalan saat rilis. Proses pengujian perangkat lunak pada aplikasi GA system 2 United Tractors saat ini masih menggunakan pengujian manual sehingga masih tergantung dengan peran manusia dan hal ini berdampak pada sisi keakuratan hasil pengujian. Penelitian ini bertujuan untuk menguji peran teknik BDD dalam implementasi automation testing pada Aplikasi GA System 2 United Tractors serta membandingkan hasil pengujian antara metode automation testing dan manual testing. Penelitian ini menggunakan metode automation testing dengan teknik behavior driven development (BDD) pada Aplikasi GA System 2 United Tractors, dengan fokus pada fitur tender. Hasil pengujian menunjukkan bahwa implementasi automation testing dengan teknik BDD pada Aplikasi GA System 2 United Tractors dapat mempercepat proses pengujian, meningkatkan efisiensi waktu dalam pengembangan aplikasi, dan mengurangi risiko bug saat rilis kepada pengguna. Pengujian automation juga menunjukkan perbandingan waktu yang lebih baik, dengan rasio 4:15 pada fitur tender Aplikasi GA System 2 United Tractors. Berdasarkan hasil penelitian, dapat disimpulkan bahwa penggunaan automation testing dengan teknik BDD merupakan pendekatan yang efektif dan efisien dalam pengujian perangkat lunak, terutama dalam menguji fitur tender pada Aplikasi GA System 2 United Tractors. Penelitian ini membuktikan bahwa pengujian automation dengan pendekatan BDD merupakan solusi yang efektif dalam meningkatkan kualitas dan keseluruhan pengujian perangkat lunak.